O ORNITORRINCO: Cursinho Popular na Imprensa de Ponta Grossa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The master's research presents a study on the popular pre-college courses in the municipality of Ponta Grossa. The interest in carrying out this research is motivated by acting as a volunteer teacher in pre-university preparatory courses and also by the studies developed in the undergraduate course in Biological Sciences, on the “Social Representations of students about pre-university preparatory courses in the municipality of Ponta Grossa” – in which the findings of the research pointed out that the social representation circulating among the students concerned: dedication, opportunity and teachers. The data collection was documentary made through printed copies of Jornal da Manhã from 2009 to 2021, which are the years in which the newspaper presents the largest number of reports about the popular course in Ponta Grossa-PR. As a general objective, we seek to analyze how the press registers access to the brazilian university and the inclusion mechanisms used. Dialectical Historical Materialism was used as a theoretical contribution, in which we worked on the issue of ideology, contradiction and mediation categories. Historically, it is from 1988, after the constitution, that some popular initiatives start across the country. a) Do the popular courses help in the “inclusion” project of low-income students, who could not afford a good high school and be able to think about a Public University? b) What difficulties do public school students have in popular courses? For theoretical support, we carried out a survey of the state of knowledge in which, in the Graduate programs in Education in the country, the following works were found: Santos (1997ab); Bachetto (2004); Bonfim (2003); Sanger (2003); Castro (2005); Ruedas (2005); Pereira (2007); Porto (2008); Nascimento (2009); Siqueira (2011); Mendes (2011) deepening our state of knowledge in History of Education, dissertations and theses that deal with this theme so that we know how original our research is. To answer our questions, the research has the general objective: To identify in the press of Ponta Grossa/PR the treatment given to popular courses, in order to reveal the intentionality of the sources. As specific objectives: Analyze in the press what is publicized about pre-college courses popular in the municipality of Ponta Grossa; Check how the reasons why students seek to attend college preparatory courses are represented in the press; With this work, we were able to understand why we need these social movements, showing the importance of these spaces and the vision of interests of these means of dissemination about popular courses.
Keywords: Cursinhos Populares; Imprensa; Materialismo Histórico Dialético; Popular courses; Press; Dialectical Historical Materialism; CNPQ::CIENCIAS HUMANAS::EDUCACAO